Passive Leg Raising After Left Ventricular Assist Device Implantation. Issue 7 (September 2019) - Ram, Eilon; Dourov, Daniil; Berkenstadt, Haim; Lavee, Jacob; Kassif, Yigal; Peled-Potashnik, Yael; Kogan, Dina; Preisman, Sergey; Raanani, Ehud; Kogan, Alexander
Abstract : Left ventricular assist device (LVAD) implantation is a common procedure in patients with end-stage heart failure. Although optimal fluid management is essential for acceptable postoperative treatment, it is critical to identify which patients will benefit from fluid administration. Passive leg raising (PLR) is a validated dynamic method that predicts fluid responsiveness in patients with heart failure by inducing a transient increase in cardiac preload. We performed a prospective study on 20 consecutive patients who underwent PLR maneuvers after LVAD implantation. Left ventricular assist device flow, end-tidal carbon dioxide, central venous pressure (CVP), and mean arterial pressure (MAP) were measured before and after PLR. Passive leg raising responsiveness was defined as at least a 15% increase in LVAD flow: (11 were responders and 9 nonresponders). Of the responders, 7 had right ventricular dysfunction (≥3). Passive leg raising responsiveness was associated with an increase of 19% in the LVAD flow, the mean CVP was raised from 11.3 to 14.4 mm Hg and the MAP from 82.6 to 86.7 mm Hg. After PLR, end-tidal carbon dioxide was increased by 4.6 mm Hg in the responders and 1.1 mm Hg in the nonresponders. The PLR maneuver is a noninvasive and easy to perform method that uses LVAD flow to assess fluid responsiveness in patients with heart failure after LVAD implantation.